Spectrum of Lesions in Urinary Bladder- A Histopathological Study - Shah, Anita; Srivastava, Manglesh; Samdurkar, Ashok; Sigdel, Ghanshyam (Journal of Universal College of Medical Sciences, 2018)
Introduction: The lesions of urinary bladder both non-neoplastic and neoplastic pose a common source of both morbidity and mortality. An accurate diagnosis of these lesions requires cystoscopy which allows a direct visualization of the bladder mucosa and biopsies of suspected lesions. Urinary bladder cancer is sixth most common cancer worldwide and represents a heterogeneous group of neoplasms. The current study aimed to study the different bladder lesions and its clinical features to detect it in early stage and as a mainstay option in the diagnosis and follow up. Materials and methods: This was a retrospective analysis of biopsies of urinary bladder submitted to the department of pathology over a period of 12 months. The study was approved by the institutional review board of the Universal College of Medical Sciences (UCMS-TH). All the urinary bladder biopsies received in the department were included in the study whereas autolysis of specimen and inadequate biopsies were excluded. Results: Among the 36 cases of urinary bladder lesions, the majority (35.36%) were in age group 61-70 years (22.33%). The patients had combination of lower urinary tract symptoms, the commonest being hematuria. 30.55% had non-neoplastic lesions and 69.55% had neoplastic lesion. Among non- neoplastic cases, 5.55% had chronic granulomatous inflammation. Most common neoplastic lesions was infiltrating urothelial carcinoma (n=6) followed by non- invasive urothelial neoplasia (n=5). Conclusion: A variety of lesions occur in urinary bladder and is commonly encountered by pathologist. Hematuria was commonest symptom and the clinicians investigated these patients further, which led to discovery of the urothelial tumors. Identification of these patients has an important impact on prognosis as well as on therapeutic approach.